Whooper Swan Cygnus cygnus January population censuses for Northwest Mainland Europe, 1995–2015 - Laubek, Bjarke; Clausen, Preben; Nilsson, Leif; Wahl, Johannes; Wieloch, Maria; Meissner, Włodzimierz; Shimmings, Paul; Larsen, Bjørn-Harald; Hornman, Menno; Langendoen, Tom; Lehikoinen, Aleksi; Luigujõe, Leho; et al. (Wildfowl, 2019)
Internationally coordinated censuses of Whooper Swans Cygnus cygnus across continental northwest Europe were undertaken in mid-winter 1995, 2000, 2005, 2010 and 2015. The estimate of 138,500 birds in 2015, the highest to date, represented a more than doubling of the population size (at an annual increase of 4.1%) since the first census total of 59,000 swans in 1995. The largest increase was in Denmark, where numbers almost trebled from 21,740 in 1995 to 62,620 in 2015. More than 97% of all swans were counted in just six countries. The percentage of total numbers increased significantly between 1995 and 2015 in Denmark (from 36.5% to 45.2%) and Germany (26.0% to 34.7%), but declined significantly in Sweden (14.2% to 8.4%), Norway (13.1% to 3.6%), Poland (6.2% to 4.0%) and the Netherlands (2.4% to 1.7%). The counts show an increasing discrepancy between national trends in abundance for Whooper Swans in Sweden and especially in Denmark in comparison with results obtained only from mid-winter International Waterbird Count (IWC) site coverage. This demonstrates the increasing tendency for Whooper Swans to winter in areas away from traditionally counted IWC sites and confirms the continued need for a regular cycle of coordinated dedicated swan counts to anchor population trends generated from other data sources.